1999
DOI: 10.1093/rheumatology/38.12.1228
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pregnancy loss and autoantibody profile in autoimmune diseases

Abstract: In women with autoimmune disorders, a history of recurrent pregnancy loss is independently associated with reactivity against each of the three antigen specificities (Ro52, Ro60, p57) and also with the presence of antithyroglobulin antibodies, suggesting that cumulative autoimmune responses against these non-organ-specific and organ-specific antigens correlate with the risk of stillbirth and spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In subjects without SLE, autoantibodies have been described to occur in association with premature ovarian failure 22 and anti-nuclear antibodies have been proposed actually as a marker of a specific subtype of premature ovarian failure occurring before age 30. 23 Interestingly, anti-Ro is the strongest predictor of fetal wastage in SLE 24 and of neonatal congenital heart block. 25 Anti-U1RNP associations are less clear-cut, although this antibody has been associated with neonatal lupus without congenital heart block.…”
Section: Gonadal Toxicitymentioning
confidence: 99%
“…In subjects without SLE, autoantibodies have been described to occur in association with premature ovarian failure 22 and anti-nuclear antibodies have been proposed actually as a marker of a specific subtype of premature ovarian failure occurring before age 30. 23 Interestingly, anti-Ro is the strongest predictor of fetal wastage in SLE 24 and of neonatal congenital heart block. 25 Anti-U1RNP associations are less clear-cut, although this antibody has been associated with neonatal lupus without congenital heart block.…”
Section: Gonadal Toxicitymentioning
confidence: 99%
“…Unfortunately, despite extensive investigation, an etiology is demonstrated in only 50% of recurrent aborters. To date, only one autoantibody, the anticardiolipin antibody, has been shown to correlate with pregnancy loss in women with recurrent abortion (8)(9)(10)(11)(12)(13)(14). Treatment with heparin and aspirin, in women with three or more pregnancy losses, has been shown to improve the pregnancy success rate in anticardiolipin positive women (36)(37)(38).…”
Section: Thyroid Autoantibodies and Habitual Abortionmentioning
confidence: 99%
“…This factor was later coined the lupus anticoagulant. Subsequently, multiple studies have confirmed a correlation between circulating nonorgan-specific autoantibodies, particularly the lupus anticoagulant (5-7) and the anticardiolipin antibody (8)(9)(10)(11)(12)(13)(14) and recurrent abortion. A recent study reported three additional nontissue-specific autoantibodies, those directed against Ro52, Ro60, and p57, which were also independently associated with pregnancy loss (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, antibodies to ENA (anti‐ENA) have been considered to be associated with pregnancy loss. Mavragani et al 16 . found that in women with autoimmune disorders, a history of RM was independently associated with anti‐Ro/SSA.…”
Section: Introductionmentioning
confidence: 99%